Triazole linking for preparation of a next-generation sequencing library from single-stranded DNA. Issue 16 (26th May 2018) - Miura, Fumihito; Fujino, Tomoko; Kogashi, Kanako; Shibata, Yukiko; Miura, Miki; Isobe, Hiroyuki; Ito, Takashi
Abstract: Next-generation sequencing of single-stranded DNA (ssDNA) is attracting increased attention from a wide variety of research fields. Accordingly, various methods are actively being tested for the efficient adaptor-tagging of ssDNA. We conceived a novel chemo-enzymatic method termed t erminal deoxynucleotidyl transferase (TdT)-assisted, c opper-catalyzed azide-alkyne cycloaddition (CuAAC)-mediated s sDNA ligation (TCS ligation). In this method, TdT is used to incorporate a single 3′-azide-modified dideoxyribonucleotide onto the 3′-end of target ssDNA, followed by CuAAC-mediated click ligation of the azide-incorporated 3′-end to a 5′-ethynylated synthetic adaptor. This report presents the first proof-of-principle application of TCS ligation with its use in the preparation of a next-generation sequencing library.